2013
DOI: 10.1016/j.jinf.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis B and delta virus co-infection on liver disease in Mauritania: A cross sectional study

Abstract: In Mauritania, HDV co-infection worsens liver disease, both clinically and biologically, as confirmed by the APRI and FibroMeter tests. These tests may be useful for the management of delta hepatitis, which is a major health problem in Mauritania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 36 publications
(40 reference statements)
7
45
3
1
Order By: Relevance
“…The rare HDV seroprevalence studies that have been performed during the past 15 years and the recent reports of the African clades 5 to 8 (5,6) als), Gabon (15.6% to 70.6%), Mauritania (14.7% to 33.1%), Mozambique (0%), Nigeria (0% to 12.5%), and Senegal (3.2%), revealed various HDV antibody rates (2,(15)(16)(17)(18)(19)(36)(37)(38)(39)(40). Interestingly, also in our study, the HDV Ab prevalences varied widely and ranged from 0% to 27.3% in asymptomatic carriers and from 1.3% to 50% in liver patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rare HDV seroprevalence studies that have been performed during the past 15 years and the recent reports of the African clades 5 to 8 (5,6) als), Gabon (15.6% to 70.6%), Mauritania (14.7% to 33.1%), Mozambique (0%), Nigeria (0% to 12.5%), and Senegal (3.2%), revealed various HDV antibody rates (2,(15)(16)(17)(18)(19)(36)(37)(38)(39)(40). Interestingly, also in our study, the HDV Ab prevalences varied widely and ranged from 0% to 27.3% in asymptomatic carriers and from 1.3% to 50% in liver patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 15 were attributed to these supposedly "African" clades, while 10 strains clustered with clade 1 (5,6). Despite their characterization as African clades, only few genotyping studies have been performed in Africa (Cameroon, clades 1, 5, 6, 7; Gabon, clades 1, 7, and 8; Mauritania, clades 1 and 5), and clade 1 dominated in all cohorts (2,5,6,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In Mauritania a prevalence rate of 33.1% among HBsAg positive patients was recently reported, and HDV was associated with more aggressive disease than HBV infection alone (122). Other studies show wide differences in sero-prevalence in HBsAg positive liver patients, ranging from 1.3% in a Nigerian center, to 50% in Central African Republic and 66% in Gabon (123,124).…”
Section: The Case Of Low Endemicity Regionsmentioning
confidence: 96%
“…However, it is of worthy to note that in the two previous studies, HIV& HBV co-infected patients were exclusively reported while only two HIV&HBV co-infected patients were found in the present study. In other studies elsewhere in Africa, prevalence varied from 0-50% was reported without any clear explanation on these variations [12][13][14]. In two previous studies carried out in the northern part of Benin, Zanchetta et al [7] reported 19.4% prevalence rate for anti-HDV antibodies while a rate of 11.4% was reported by de Paschale et al some years later [8].…”
Section: Discussionmentioning
confidence: 94%